Profiles of dual language education in the 21st century - Arias, M. Beatriz; Fee, Molly, 1986- (Bristol, U.K. Blue Ridge Summit, PA : Multilingual Matters, 2018)
'In the last 20 years dual language education programs have increased in number and expanded in range, spanning pre-K through high school. This book examines the key attributes of successful dual language programs, as well as the challenges and opportunities involved in extending the dual language instructional model to pre-K and secondary settings' --
Dual language programs -- 20 years of DLE: recent research on the three goals of dual language -- Education / Beatriz Arias & Amy markos -- Legacy programs: key elementary, Arlington, Virginia / Igone Arteagoitia -- Dual language bilingual education in NYC: a potential unfulfilled? / Ofelia Garcia, Kate Menken, Patricia Velasco, & Sara Vogel -- Elgin, Illinois: an entire district goes dual: the journey of a district committed to culturally and linguistically responsive instruction / Wilma Valero & Patricia Makishima -- Implementing dual language: programmatic issues -- Implications of research for dual language at the early childhood level / Kathryn Lindholm-Leary -- Opportunities and dilemmas for TWI programs at the secondary level / Carol Bearse, Ester de Jong, & Min-Chuan Tsai -- Teacher preparation for dual language classrooms / Barbara Kennedy -- Making space for dual language education: the role of policy / Donna Christian -- Conclusion: taking stock: lessons on dual language education / Fred Genesee.
Includes index and bibliographical references pages : 152-155.
Keywords: Education, Bilingual; Multicultural education; Education, Bilingual -- Case studies; Multicultural education -- Case studies